A modular approach to the specification and management of time duration constraints in BPMN. (September 2019) - Combi, Carlo; Oliboni, Barbara; Zerbato, Francesca
Abstract: The modeling and management of business processes deals with temporal aspects both in the inherent representation of activity coordination and in the specification of activity properties and constraints. In this paper, we address the modeling and specification of constraints related to the duration of process activities. In detail, we consider the Business Process Model and Notation (BPMN) standard and propose an approach to define re-usable duration-aware process models that make use of existing BPMN elements for representing different nuances of activity duration at design time. Moreover, we show how advanced event-handling techniques may be exploited for detecting the violation of duration constraints during the process run-time. The set of process models specified in this paper suitably captures duration constraints at different levels of abstraction, by allowing designers to specify the duration of atomic tasks and of selected process regions in a way that is conceptually and semantically BPMN-compliant. Without loss of generality, we refer to real-world clinical working environments to exemplify our approach, as their intrinsic complexity makes them a particularly challenging and rewarding application environment. Highlights: We represent different kinds of duration constraints through re-usable BPMN process models. The presented processes provide a clear conceptualization of duration-aware process activities. A formal description of the proposed patterns is provided along with real-world motivating examples. Being fully BPMN-compliant, the proposed approach benefits of existing tool support. The soundness of the obtained process models is verified by mapping them to time Petri nets.